Solid electrolyte composition and method for producing solid electrolyte component

By using a composition of a solid electrolyte material containing oxygen and halogen elements and a specific organic solvent, the problem of reducing the ion conductivity of the solid electrolyte material is solved, and efficient battery performance is achieved.

CN114746958BActive Publication Date: 2025-04-29PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202080083977.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-12-12
Filing Date
2020-12-09
Publication Date
2025-04-29
Estimated Expiration
2040-12-09

AI Technical Summary

Technical Problem

In the prior art, the ion conductivity of solid electrolyte materials is easily reduced, which affects battery performance.

Method used

A solid electrolyte material containing oxygen elements and halogen elements and a specific organic solvent is used to inhibit the decrease of ion conductivity by adjusting the viscosity of the composition and the selection of organic solvents.

Benefits of technology

The high ion conductivity of solid electrolyte materials and denser solid electrolyte components are achieved, and the charging and discharging efficiency of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0003993309840000151
    Figure GDA0003993309840000151
  • Figure GDA0003993309840000152
    Figure GDA0003993309840000152
  • Figure GDA0003993309840000161
    Figure GDA0003993309840000161
Patent Text Reader

Abstract

The solid electrolyte composition of the present application comprises a solid electrolyte material containing oxygen and halogen elements and an organic solvent. The organic solvent comprises at least one selected from a compound having a halogen group and a hydrocarbon. The solid electrolyte material comprises at least one selected from Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a solid electrolyte composition and a method for producing a solid electrolyte component used in the production of, for example, an all-solid-state battery. Background Art

[0002] Patent Document 1 discloses a solid electrolyte composition using a sulfide solid electrolyte.

[0003] Prior art literature

[0004] Patent Document 1: International Publication No. 2018 / 168505 Summary of the invention

[0005] Technical problem to be solved by the invention

[0006] Conventionally, it is desired to suppress the decrease in the ion conductivity of a solid electrolyte material.

[0007] Means used to solve problems

[0008] One aspect of the present application relates to a solid electrolyte composition, which comprises:

[0009] Solid electrolyte material containing oxygen element and halogen element, and

[0010] Organic solvents,

[0011] The organic solvent comprises at least one selected from a compound having a halogen group and a hydrocarbon,

[0012] The solid electrolyte material includes at least one selected from Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm.

[0013] Another aspect of the present application relates to a method for producing a solid electrolyte component, comprising the step of removing the organic solvent from the solid electrolyte composition.

[0014] Effects of the Invention

[0015] According to the present application, a solid electrolyte composition capable of suppressing a decrease in the ion conductivity of a solid electrolyte material and a method for producing a solid electrolyte component using the solid electrolyte composition can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a schematic diagram showing a method for evaluating the lithium ion conductivity of a solid electrolyte material.

[0017] Figure 2This is a graph showing the relationship between the polar term of the Hansen solubility parameter for an organic solvent and the lithium ion conductivity of the LTOC after vacuum drying.

[0018] Figure 3 This is a flow chart showing an example of a method for producing a solid electrolyte component. DETAILED DESCRIPTION

[0019] (Overview of one embodiment of the present application)

[0020] The first embodiment of the solid electrolyte composition of the present application comprises a solid electrolyte material containing oxygen and a halogen element and an organic solvent, wherein the organic solvent comprises at least one selected from a compound having a halogen group and a hydrocarbon, and the solid electrolyte material comprises at least one selected from Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm.

[0021] According to the first aspect, a decrease in the ion conductivity of the solid electrolyte material can be suppressed.

[0022] In the second aspect of the present application, for example, in the solid electrolyte composition of the first aspect, the solid electrolyte material may have lithium ion conductivity and may contain at least one selected from F, Cl, Br and I.

[0023] In the third aspect of the present application, for example, in the solid electrolyte composition of the first aspect, the solid electrolyte material may further include Li, O, at least one selected from Ta and Nb, and at least one selected from F, Cl, Br and I.

[0024] In the fourth embodiment of the present application, for example, in the solid electrolyte composition of the third embodiment, the solid electrolyte material may further include at least one selected from a material containing Li, Ta, O and Cl, a material containing Li, Nb, O and Cl, and a material containing Li, Ta, Nb, O and Cl.

[0025] In the fifth embodiment of the present application, for example, in the solid electrolyte composition of the fourth embodiment, the solid electrolyte material may include Li, O, M and Cl, the M may include at least one selected from Ta and Nb, the ratio of the molar number of O to the molar number of Cl may be greater than 0.16 and less than 0.35, and the ratio of the molar number of Li to the molar number of M may be greater than 0.6 and less than 2.4.

[0026] In the sixth aspect of the present application, for example, in the solid electrolyte composition of the fifth aspect, the solid electrolyte material may include a material selected from LiTaOCl 4 、LiNbOCl 4 and LiTa 0.9 Nb0.1 OCl 4 At least one of .

[0027] According to the second to sixth aspects, it is possible to suppress a decrease in the ion conductivity of the solid electrolyte material.

[0028] In the seventh aspect of the present application, for example, in the solid electrolyte composition of any one of the first to sixth aspects, the compound having a halogen group may have only a halogen group as a functional group. According to this configuration, a solid electrolyte composition having excellent suspension stability of a solid electrolyte material can be obtained.

[0029] In an eighth aspect of the present application, for example, in the solid electrolyte composition of any one of the first to seventh aspects, the organic solvent may further contain a ring structure.

[0030] In a ninth aspect of the present application, for example, in the solid electrolyte composition of the eighth aspect, the organic solvent may further contain an aromatic compound.

[0031] According to the eighth and ninth aspects, the oxyhalide-based solid electrolyte material can be easily dispersed in the organic solvent.

[0032] In the tenth aspect of the present application, for example, in the solid electrolyte composition of any one of the first to seventh aspects, the organic solvent may include at least one selected from tetralin, ethylbenzene, mesitylene, pseudocumene, xylene, cumene, 1,2,4-trichlorobenzene, chlorobenzene, 2,4-dichlorobenzene, o-chlorotoluene, 1,3-dichlorobenzene, p-chlorotoluene, 1,2-dichlorobenzene, 1,4-dichlorobutane, 2,4-dichlorotoluene and 3,4-dichlorotoluene.

[0033] In the eleventh embodiment of the present application, for example, in the solid electrolyte composition of any one of the first to seventh embodiments, the organic solvent may include at least one selected from tetralin, mesitylene, xylene, cumene, o-chlorotoluene, p-chlorotoluene, 1,4-dichlorobutane, 2,4-dichlorotoluene and 3,4-dichlorotoluene.

[0034] According to the tenth and eleventh aspects, the oxyhalide-based solid electrolyte material can be easily dispersed in the organic solvent.

[0035] In the twelfth aspect of the present application, for example, in the solid electrolyte composition of any one of the first to eleventh aspects, the solid electrolyte material may contain substantially no sulfur element. According to the twelfth aspect, a decrease in ion conductivity of the solid electrolyte material can be more reliably suppressed.

[0036] A method for producing a solid electrolyte component according to a thirteenth aspect of the present application includes removing the organic solvent from the solid electrolyte composition according to any one of the first to twelfth aspects.

[0037] According to the thirteenth aspect, a homogeneous solid electrolyte membrane can be manufactured.

[0038] In the fourteenth aspect of the present application, for example, in the method for producing a solid electrolyte member according to the thirteenth aspect, the organic solvent may be removed by drying under reduced pressure. According to such a configuration, a coating film having a uniform thickness can be formed.

[0039] Below, while referring to the attached Figure 1 Embodiments of the present invention will be described below.

[0040] <The inventor’s perspective>

[0041] In the past, in the field of secondary batteries that require high energy density and large capacity, the mainstream has been to use an organic electrolyte solution in which an electrolyte salt is dissolved in an organic solvent. Secondary batteries using organic electrolyte solutions have been pointed out to have concerns about leakage and the possibility of increased heat generation when a short circuit occurs.

[0042] On the other hand, all-solid secondary batteries that use inorganic solid electrolytes instead of organic electrolytes are attracting attention. All-solid secondary batteries do not leak. Since inorganic solid electrolytes are not flammable, it is expected that heat generation during short circuits can be suppressed.

[0043] As inorganic solid electrolytes used in all-solid secondary batteries, sulfide-based solid electrolytes containing sulfur as the main component and oxide-based solid electrolytes containing metal oxides as the main component are known. However, sulfide-based solid electrolytes sometimes produce toxic hydrogen sulfide when reacting with water. Oxide-based solid electrolytes have low ion conductivity. Therefore, it is expected to develop a new solid electrolyte material with excellent ion conductivity.

[0044] As a new type of solid electrolyte material, for example, an oxyhalide solid electrolyte material containing lithium, tantalum, oxygen, and at least one halogen element is expected. An oxyhalide solid electrolyte is a solid electrolyte containing oxygen and a halogen element.

[0045] In order to put all-solid secondary batteries using solid electrolyte materials into practical use, a technique is required in which a composition having fluidity including the solid electrolyte material is prepared and applied on the surface of an electrode or a current collector to form a solid electrolyte member.

[0046] In order to prepare a fluid composition, it is necessary to mix the solid electrolyte material with an organic solvent. Therefore, the inventors studied the tolerance of oxyhalide solid electrolyte materials to various organic solvents. The results show that when a specific organic solvent is mixed with an oxyhalide solid electrolyte material, the lithium ion conductivity of the oxyhalide solid electrolyte material is sometimes reduced. For example, even an organic solvent that can be used in a sulfide solid electrolyte may not be used in an oxyhalide solid electrolyte material. From the above perspectives, the composition of the present application is obtained.

[0047] (Implementation Method 1)

[0048] The solid electrolyte composition in Embodiment 1 includes a solid electrolyte material containing an oxygen element and a halogen element, and an organic solvent.

[0049] The solid electrolyte composition may be in a paste state or in a dispersion state. The solid electrolyte material is, for example, in a particle state. In the solid electrolyte composition, particles of the solid electrolyte material are mixed with an organic solvent. The viscosity of the solid electrolyte composition may be appropriately adjusted. For example, when applied by a method such as a spray method, the viscosity of the solid electrolyte composition is relatively low. When applied by a method such as a scraper method, the viscosity of the solid electrolyte composition is relatively high.

[0050] The ratio of the weight of the solid electrolyte material to the total weight of the solid electrolyte material and the weight of the organic solvent is not particularly limited and may be 70 wt % or less. With this configuration, a solid electrolyte composition that can be easily applied to the surface of an electrode or a current collector can be obtained.

[0051] The organic solvent includes at least one selected from a compound having a halogen group and a hydrocarbon. These organic solvents have, for example, desired polarity, and therefore can have appropriate interactions with respect to the solid electrolyte material. As a result, the solid electrolyte material is easy to stably maintain its structure even if it is dispersed in these organic solvents. As a result, a solid electrolyte material capable of suppressing the reduction of ion conductivity can be obtained.

[0052] Hydrocarbons are compounds formed only of carbon and hydrogen. Hydrocarbons may be aliphatic hydrocarbons. Hydrocarbons may be saturated hydrocarbons or unsaturated hydrocarbons. Hydrocarbons may be straight-chain or branched. The number of carbon atoms contained in the hydrocarbon is not particularly limited and may be 7 or more. By using hydrocarbons, a solid electrolyte composition having excellent suspension stability of the solid electrolyte material can be obtained.

[0053] The hydrocarbon may also have a ring structure. The hydrocarbon may also have an aromatic ring. The ring structure may be an alicyclic hydrocarbon or an aromatic hydrocarbon. The ring structure may be a monocyclic hydrocarbon or a polycyclic hydrocarbon. By making the hydrocarbon have a ring structure, the oxyhalide solid electrolyte material can be easily dispersed in an organic solvent. From the viewpoint of improving the suspension stability of the oxyhalide solid electrolyte material in the solid electrolyte composition, the hydrocarbon may also contain an aromatic hydrocarbon. The hydrocarbon may also be an aromatic hydrocarbon.

[0054] The compound having a halogen group may be a compound in which the part other than the halogen group is formed only of carbon and hydrogen. That is, the compound having a halogen group may be a compound in which at least one of the hydrogen atoms contained in the hydrocarbon is replaced by a halogen group. As the halogen group, F, Cl, Br and I can be mentioned. As the halogen group, at least one selected from F, Cl, Br and I can be used, and multiple types can also be used. From the viewpoint of boiling point or dryness, the halogen group may be a chlorine group. The compound having a halogen group may have high polarity. By using a compound having a halogen group, a halogen oxide-based solid electrolyte material can be easily dispersed in a solid electrolyte composition. Therefore, a solid electrolyte composition having excellent suspension stability of the solid electrolyte material can be obtained. As a result, the solid electrolyte composition can form a solid electrolyte component having excellent lithium ion conductivity and being more dense.

[0055] The number of carbons contained in the compound having a halogen group is not particularly limited, and may be 7 or more. Thus, the compound having a halogen group is not easily volatile, and thus a solid electrolyte composition can be stably manufactured. In addition, the compound having a halogen group may have a large molecular weight. That is, the compound having a halogen group may have a high boiling point.

[0056] The compound having a halogen group may have a ring structure. The compound having a halogen group may have an aromatic ring. The ring structure may be an alicyclic hydrocarbon or an aromatic hydrocarbon. The ring structure may be a monocyclic or a polycyclic. By making the compound having a halogen group have a ring structure, the oxyhalide-based solid electrolyte material can be easily dispersed in the compound having a halogen group. The compound having a halogen group may include an aromatic hydrocarbon. The compound having a halogen group may also be an aromatic compound.

[0057] The compound having a halogen group may have only a halogen group as a functional group. In this case, the number of halogen groups contained in the compound having a halogen group is not particularly limited. As a halogen, at least one selected from F, Cl, Br and I can be used, or multiple types can be used. By using such a compound, in a solid electrolyte composition, a halogen oxide-based solid electrolyte material can be easily dispersed. Therefore, a solid electrolyte composition having excellent suspension stability of the solid electrolyte material can be obtained. As a result, the solid electrolyte composition can form a solid electrolyte component having excellent lithium ion conductivity and being more dense. By using such a compound, the solid electrolyte composition can, for example, easily form a dense solid electrolyte membrane with few pinholes, bumps, etc.

[0058] As described above, the compound having a halogen group may be a compound in which at least one of the hydrogen atoms contained in the hydrocarbon is replaced by a halogen group. That is, the compound having a halogen group may be a halogenated hydrocarbon. The compound having a halogen group may be a compound in which all the hydrogen atoms contained in the hydrocarbon are replaced by halogen atoms. By using a halogenated hydrocarbon, the oxyhalide solid electrolyte material can be easily dispersed in the solid electrolyte composition. Therefore, a solid electrolyte composition having excellent suspension stability of the solid electrolyte composition can be obtained. As a result, the solid electrolyte composition can form a solid electrolyte component having excellent lithium ion conductivity and being more dense. By using a halogenated hydrocarbon, the solid electrolyte composition can, for example, easily form a dense solid electrolyte membrane with few pinholes, bumps, etc.

[0059] More specifically, the organic solvent may include at least one selected from tetralin, ethylbenzene, mesitylene, pseudocumene, xylene, cumene, 1,2,4-trichlorobenzene, chlorobenzene, 2,4-dichlorobenzene, o-chlorotoluene, 1,3-dichlorobenzene, p-chlorotoluene, 1,2-dichlorobenzene, 1,4-dichlorobutane, 2,4-dichlorotoluene and 3,4-dichlorotoluene. With this configuration, the solid electrolyte material containing oxygen and halogen elements can be easily dispersed in the organic solvent. With this configuration, the oxyhalide solid electrolyte material can be easily dispersed in the organic solvent.

[0060] More specifically, the organic solvent may include at least one selected from tetralin, mesitylene, xylene, cumene, o-chlorotoluene, p-chlorotoluene, 1,4-dichlorobutane, 2,4-dichlorotoluene, and 3,4-dichlorotoluene. With this configuration, the solid electrolyte material containing oxygen and halogen elements can be easily dispersed in the organic solvent. With this configuration, the oxyhalide-based solid electrolyte material can be easily dispersed in the organic solvent.

[0061] The organic solvent may contain at least one selected from a compound having a halogen group and a hydrocarbon. The number of halogen groups contained in the molecules of the organic solvent is not particularly limited. The number of halogen groups contained in the molecules of the organic solvent may be one. The boiling point of the organic solvent is not particularly limited and may be above 100°C and below 250°C. The organic solvent may be a liquid at room temperature (25°C). Since such an organic solvent is not easily volatile at room temperature, a solid electrolyte composition can be stably manufactured. Therefore, a solid electrolyte composition that can be easily applied to the surface of an electrode or a collector can be obtained. In addition, the organic solvent can be easily removed by drying. The organic solvent can be any liquid capable of dispersing the oxyhalide solid electrolyte material, and the oxyhalide solid electrolyte material may not be completely dissolved in the organic solvent.

[0062] The organic solvent may not contain heteroatoms. With this structure, the oxyhalide solid electrolyte material can be easily dispersed in the organic solvent. Examples of heteroatoms are N, O, P and S.

[0063] The value of the polar term δp in the Hansen Solubility Parameter (HSP) of an organic solvent is not limited to a specific value. HSP is a parameter that represents the solubility characteristics between substances. In the present application, HSP refers to a parameter that decomposes the Hildebrand solubility parameter into a vector of three cohesive energy components: London dispersion force, dipole force, and hydrogen bonding force. In the present application, the component corresponding to the dipole force of HSP is recorded as the polar term δp. The unit of δp is, for example, MPa. 1 / 2 The HSP value of the organic solvent can be obtained, for example, by referring to a database. In the case of an organic solvent whose HSP value is not registered in a database, the HSP value can be calculated from the chemical structure of the organic solvent by using computer software such as Hansen Solubility Parameters in Practice (HSPiP).

[0064] The value of the polar term δp in the HSP of an organic solvent is, for example, 0 MPa. 1 / 2 Above and 12.0MPa 1 / 2 As a result, the oxyhalide solid electrolyte material can be easily dispersed in the solid electrolyte composition. When the organic solvent contains a compound having a halogen group, the polar term δp value in the HSP of the organic solvent can be 3.0 MPa. 1 / 2 Above and 11.0MPa 1 / 2 Below, can also be 4.0MPa 1 / 2 Above and 10.0MPa 1 / 2 When the organic solvent contains hydrocarbons, the polar term δp value in the HSP of the organic solvent may be 0 MPa. 1 / 2 Above and 3.0MPa1 / 2 Below, can also be 0.5MPa 1 / 2 Above and 2.5MPa 1 / 2 the following.

[0065] By the above configuration, the solid electrolyte composition can suppress the decrease of ion conductivity. That is, when the solid electrolyte composition containing the solid electrolyte material containing oxygen element and halogen element and the organic solvent is dried and the organic solvent is removed, a solid electrolyte component with high ion conductivity can be obtained. The solid electrolyte component can be a solid electrolyte membrane.

[0066] The oxyhalide-based solid electrolyte material may have lithium ion conductivity, for example.

[0067] The oxyhalide solid electrolyte material includes at least one selected from Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm. In the oxyhalide solid electrolyte material, these elements may exist in a state having a valence other than divalent. In the oxyhalide solid electrolyte material, these elements may exist in a state having a valence greater than divalent.

[0068] The oxyhalide-based solid electrolyte material may further contain at least one selected from F, Cl, Br, and I.

[0069] According to the above configuration, the solid electrolyte composition can further suppress the reduction of lithium ion conductivity, thereby making it possible to produce a solid electrolyte component having higher lithium ion conductivity.

[0070] The oxyhalide-based solid electrolyte material may further include Li, O, at least one selected from Ta and Nb, and at least one selected from F, Cl, Br, and I.

[0071] With the above-described configuration, the solid electrolyte composition can more reliably suppress a decrease in lithium ion conductivity, thereby making it possible to produce a solid electrolyte component having higher lithium ion conductivity.

[0072] More specifically, the oxyhalide solid electrolyte material may further include at least one selected from a material containing Li, Ta, O and Cl, a material containing Li, Nb, O and Cl, and a material containing Li, Ta, Nb, O and Cl. The oxyhalide solid electrolyte material may also be a material containing Li, Ta, O and Cl, a material containing Li, Nb, O and Cl, or a material containing Li, Ta, Nb, O and Cl.

[0073] The oxyhalide solid electrolyte material may also be a metal oxyhalide compound. The metal oxyhalide compound contains Li, M, O, and X, for example.

[0074] Here, M includes, for example, at least one selected from Nb and Ta. In addition, X is at least one selected from Cl, Br, and I.

[0075] The metal oxyhalide compound includes, for example, Li, M, O and Cl. In the oxyhalide solid electrolyte material, the ratio of the number of moles of O to the number of moles of Cl, i.e., O / Cl, can be greater than 0.16 and less than 0.35. In the oxyhalide solid electrolyte material, the ratio of the number of moles of Li to the number of moles of M, i.e., Li / M, can be greater than 0.6 and less than 2.4. With this configuration, the solid electrolyte composition can further suppress the reduction of lithium ion conductivity. Thus, a solid electrolyte component with higher lithium ion conductivity can be manufactured.

[0076] M may be Ta and Nb. In the metal oxyhalide compound, the ratio of the number of moles of O to the number of moles of Cl, i.e., O / Cl, may be greater than 0.16 and less than 0.35. In the metal oxyhalide compound, the ratio of the number of moles of Li to the sum of the number of moles of Ta and Nb, i.e., Li / (Ta+Nb), may be greater than 0.6 and less than 2.4. With this configuration, the solid electrolyte composition can further suppress the reduction in lithium ion conductivity. Thus, a solid electrolyte component having higher lithium ion conductivity can be manufactured.

[0077] The metal halide oxide compound can be represented by the following composition formula (A). In the composition formula (A), a can satisfy 0.1<a<7.0. b can satisfy 0.4<b<1.9. The metal halide oxide compound shown in the composition formula (A) can have high ionic conductivity. By using the metal halide oxide compound as a solid electrolyte material, the all-solid-state battery can exhibit excellent charge and discharge efficiency.

[0078] Li a MO b X 5+a-2b (A)

[0079] Examples of metal halide oxide compounds represented by composition formula (A) include: LiTaOCl 4 、LiNbOCl 4 and LiTa 0.9 Nb 0.1 OCl 4 The solid electrolyte material may include a material selected from LiTaOCl 4 、LiNbOCl 4 and LiTa 0.9 Nb 0.1 OCl 4 At least one of the solid electrolyte material may be LiTaOCl 4、LiNbOCl 4 , or LiTa 0.9 Nb 0.1 OCl 4 These metal oxyhalide compounds have high ionic conductivity. By using metal oxyhalide compounds as solid electrolyte materials, all-solid-state batteries can exhibit excellent charge and discharge efficiency.

[0080] The oxyhalide solid electrolyte material may contain substantially no sulfur. "Substantially no" means that, for example, the ratio of the molar number of S to the molar number of O, that is, S / O, in the oxyhalide solid electrolyte material is 0 or more and 0.01 or less, or the content of sulfur contained in the oxyhalide solid electrolyte material is 1 mol% or less. Thus, an oxyhalide solid electrolyte material in which the decrease in ion conductivity is more reliably suppressed can be provided. The oxyhalide solid electrolyte material may contain no sulfur.

[0081] The oxyhalide solid electrolyte material may contain crystalline substances and may also contain amorphous substances. At least a portion of the oxyhalide solid electrolyte material may be amorphous. "Amorphous" is not limited to substances that have no crystal structure at all, but also includes substances that have crystalline regions within a short-range order range. Amorphous substances refer to substances that do not show sharp peaks of crystal origin and show broad peaks of amorphous origin in X-ray diffraction (XRD), for example.

[0082] (Implementation Method 2)

[0083] Embodiment 2 will be described below. The same description as that of Embodiment 1 will be appropriately omitted. Figure 3 This is a flow chart showing an example of a method for producing a solid electrolyte component.

[0084] The method for producing a solid electrolyte component includes a step S1000 of removing an organic solvent from the solid electrolyte composition in the above-mentioned embodiment 1. The solid electrolyte component is a component containing an oxyhalide-based solid electrolyte material. For example, the solid electrolyte component may be a component such as a solid electrolyte layer containing an oxyhalide-based solid electrolyte material, a solid electrolyte membrane, or an electrode layer containing an oxyhalide-based solid electrolyte material.

[0085] By removing the organic solvent from the solid electrolyte composition containing the oxyhalide-based solid electrolyte material and the organic solvent, for example, a homogeneous solid electrolyte membrane can be produced. As a result, the solid electrolyte member can have high lithium ion conductivity.

[0086] Before removing the organic solvent from the solid electrolyte composition, the solid electrolyte composition can be applied to a substrate to form a film of the solid electrolyte composition. By removing the organic solvent from the film of the solid electrolyte, for example, a homogeneous solid electrolyte film can be manufactured. The substrate is not particularly limited. Examples of the substrate include electrodes and current collectors.

[0087] In step S1000, the organic solvent is removed from the solid electrolyte composition. At this time, the organic solvent can be removed by drying under reduced pressure. The solid electrolyte composition before the organic solvent is removed has fluidity, so it can form a coating film with excellent formability, such as a uniform thickness. If such a coating film is dried, for example, a dense solid electrolyte membrane with few pinholes, bumps, etc. can be easily obtained.

[0088] Reduced pressure drying refers to removing the organic solvent from the solid electrolyte composition in a pressure atmosphere below atmospheric pressure. The pressure atmosphere below atmospheric pressure can be, for example, -0.01 MPa or less in gauge pressure. During reduced pressure drying, the solid electrolyte composition or solid electrolyte component can also be heated to, for example, 50°C or more and 250°C or less. The organic solvent can be removed by vacuum drying. Vacuum drying, for example, refers to removing the organic solvent from the solid electrolyte composition below the vapor pressure at a temperature 20°C lower than the boiling point of the organic solvent. The removal of the organic solvent can be confirmed, for example, by Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), gas chromatography (GC) or gas chromatography mass spectrometry (GC / MS). In addition, as long as the dried solid electrolyte material has ionic conductivity, the organic solvent may not be completely removed.

[0089] Example

[0090] Hereinafter, the details of the present application will be described using Examples and Comparative Examples.

[0091] (Preparation of Solid Electrolyte Composition)

[0092] As a solid electrolyte, weigh 200 mg of LiTaOCl 4 (hereinafter referred to as LTOC), LiNbOCl 4 (hereinafter referred to as LNOC) or LiTa 0.9 Nb 0.1 OCl 4 (hereinafter referred to as LTNOC) was placed in a commercially available glass spiral tube. 100 mg of an organic solvent was weighed and placed in the spiral tube, and stirred and mixed with a spatula to prepare a solid electrolyte composition of each example.

[0093] As a solid electrolyte, weigh 150 mg of Li 2SP 2 S 5 (hereinafter referred to as LPS) was placed in another commercially available glass spiral tube. 150 mg of an organic solvent was weighed and placed in the spiral tube, and stirred and mixed with a spatula to prepare a solid electrolyte composition of a partial comparative example.

[0094] (Removal of organic solvent by drying)

[0095] The solid electrolyte component is obtained by removing the organic solvent from the solid electrolyte composition by vacuum drying. The solid electrolyte composition is vacuum dried at 100°C for 1 hour in a pressure atmosphere below the vapor pressure at a temperature 20°C lower than the boiling point of the organic solvent contained in the solid electrolyte composition. The removal of the organic solvent is confirmed by visual inspection. In the case where it is visually judged that a powder of the solid electrolyte material is obtained, it is judged as "can be dried". In the case where it is visually judged that the solid electrolyte composition is in liquid form, it is judged as "cannot be dried". In the case of "cannot be dried", the lithium ion conductivity is not measured.

[0096] (Determination of lithium ion conductivity)

[0097] Figure 1 This is a diagram for explaining a method for evaluating the lithium ion conductivity of a solid electrolyte material. Figure 1 As shown, the press-forming die 200 is composed of a frame 201, a punch upper portion 203, and a punch lower portion 202. The frame 201 is made of electrically insulating polycarbonate. The punch upper portion 203 and the punch lower portion 202 are both made of stainless steel.

[0098] use Figure 1 The ion conductivity of the press-forming mold 200 shown was evaluated by the following method.

[0099] The powder 100 of the solid electrolyte material was filled into a press mold 200 in a dry atmosphere with a dew point of -50°C or less, and uniaxially pressed at 300 MPa to produce a conductivity measurement cell of the powder of the solid electrolyte material.

[0100] While maintaining the pressure, the lead wires were taken out from the punch upper part 203 and the punch lower part 202, respectively, and connected to a potentiostat (Bio-Logic, EC-Lab) equipped with a frequency response analyzer. The lithium ion conductivity at 25°C was measured by electrochemical impedance spectroscopy.

[0101] <Example 1>

[0102] Tetralin was used as an organic solvent. LTOC, LNOC, or LTNOC was used as a solid electrolyte material, and three solid electrolyte compositions were prepared by the above method. Furthermore, tetralin as an organic solvent was removed by the above vacuum drying, and three solid electrolyte components were obtained.

[0103] The lithium ion conductivity of the obtained solid electrolyte component was measured by the above-mentioned method. The results are shown in Table 1.

[0104] <Reference example>

[0105] Four types of solid electrolyte components were obtained by the same method as in Example 1, except that no organic solvent was used and LTOC, LNOC, LTNOC or LPS was used as the solid electrolyte material.

[0106] <Example 2>

[0107] A solid electrolyte component was obtained by the same method as in Example 1 except that mesitylene was used as the organic solvent and LTOC was used as the solid electrolyte material.

[0108] <Example 3>

[0109] Three types of solid electrolyte components were obtained by the same method as in Example 1 except that xylene was used as the organic solvent.

[0110] <Example 4>

[0111] Three types of solid electrolyte components were obtained by the same method as in Example 1 except that cumene was used as the organic solvent.

[0112] <Example 5>

[0113] A solid electrolyte component was obtained by the same method as in Example 1 except that 2,4-dichlorotoluene was used as the organic solvent and LTOC was used as the solid electrolyte material.

[0114] <Example 6>

[0115] A solid electrolyte component was obtained by the same method as in Example 1 except that o-chlorotoluene was used as the organic solvent and LTOC was used as the solid electrolyte material.

[0116] <Example 7>

[0117] Three types of solid electrolyte components were obtained by the same method as in Example 1 except that p-chlorotoluene was used as the organic solvent.

[0118] <Example 8>

[0119] A solid electrolyte component was obtained by the same method as in Example 1 except that 1,4-dichlorobutane was used as the organic solvent and LTOC was used as the solid electrolyte material.

[0120] <Example 9>

[0121] Three types of solid electrolyte components were obtained by the same method as in Example 1 except that 3,4-dichlorotoluene was used as the organic solvent.

[0122] <Comparative Example 1>

[0123] A solid electrolyte component was obtained by the same method as in Example 1 except that LPS was used as the solid electrolyte material.

[0124] <Comparative Example 2>

[0125] A solid electrolyte component was obtained by the same method as in Example 1 except that mesitylene was used as the organic solvent and LPS was used as the solid electrolyte material.

[0126] <Comparative Example 3>

[0127] A solid electrolyte component was obtained by the same method as in Example 1 except that xylene was used as the organic solvent and LPS was used as the solid electrolyte material.

[0128] <Comparative Example 4>

[0129] A solid electrolyte component was obtained by the same method as in Example 1 except that cumene was used as the organic solvent and LPS was used as the solid electrolyte material.

[0130] <Comparative Example 5>

[0131] A solid electrolyte component was obtained by the same method as in Example 1 except that o-chlorotoluene was used as the organic solvent and LPS was used as the solid electrolyte material.

[0132] <Comparative Example 6>

[0133] A solid electrolyte component was obtained by the same method as in Example 1 except that p-chlorotoluene was used as the organic solvent and LPS was used as the solid electrolyte material.

[0134] <Comparative Example 7>

[0135] A solid electrolyte component was obtained by the same method as in Example 1 except that 1,4-dichlorobutane was used as the organic solvent and LPS was used as the solid electrolyte material.

[0136] <Comparative Example 8>

[0137] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that dibutyl ether was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0138] <Comparative Example 9>

[0139] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that anisole was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0140] <Comparative Example 10>

[0141] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that tetraethyl orthosilicate was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0142] <Comparative Example 11>

[0143] Three types of solid electrolyte components were obtained by the same method as in Example 1 except that butyl acetate was used as the organic solvent and LTOC, LNOC, or LPS was used as the solid electrolyte material.

[0144] <Comparative Example 12>

[0145] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that diisobutyl ketone was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0146] <Comparative Example 13>

[0147] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that N,N-dimethylaniline was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0148] <Comparative Example 14>

[0149] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that N-methylaniline was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0150] <Comparative Example 15>

[0151] Two types of solid electrolyte components were obtained by the same method as in Example 1, except that 2-ethyl-1-hexanol was used as the organic solvent and LTOC or LPS was used as the solid electrolyte material.

[0152] Tables 1 to 3 show the results of measuring the lithium ion conductivity of a solid electrolyte component formed by a solid electrolyte composition containing an organic solvent and a solid electrolyte material. As oxyhalide solid electrolyte materials, LTOC, LNOC and LTNOC were used. As a sulfide solid electrolyte material, LPS was used. The compound name of the organic solvent contained in the solid electrolyte composition, the polar term δp in the Hansen solubility parameter for the organic solvent, the skeleton structure of the organic solvent, the functional group of the organic solvent and the boiling point of the organic solvent are shown in Tables 1 to 3. Furthermore, the lithium ion conductivity of LTOC, the lithium ion conductivity of LNOC, the lithium ion conductivity of LTNOC and the lithium ion conductivity of LPS are shown in Tables 1 to 3.

[0153] Table 1

[0154]

[0155] Table 2

[0156]

[0157] Table 3

[0158]

[0159] The solid electrolyte component of the embodiment shows high lithium ion conductivity. The lithium ion conductivity of the solid electrolyte component of the embodiment is comparable to that of the solid electrolyte component of the reference example. By using the organic solvent of the embodiment, the decrease in lithium ion conductivity when the solid electrolyte component is made from the solid electrolyte composition is suppressed.

[0160] When LTOC was used as the oxyhalide solid electrolyte material, the lithium ion conductivity of the solid electrolyte components of Comparative Examples 8 to 10 and 12 was lower than that of the solid electrolyte component of the reference example. Therefore, the use of the organic solvents of Comparative Examples 8 to 10 and 12 did not suppress the reduction in lithium ion conductivity of the solid electrolyte component. The reason for this is believed to be that the organic solvents of Comparative Examples 8 to 10 and 12 were adsorbed on the solid electrolyte material.

[0161] When butyl acetate, N,N-dimethylaniline, N-methylaniline, or 2-ethyl-1-hexanol is used as the organic solvent, the organic solvent cannot be removed in the preparation of the solid electrolyte component containing the oxyhalide solid electrolyte material. By using a compound having a functional group other than a halogen group in the organic solvent, the solid electrolyte material reacts with the compound having a functional group other than a halogen group.

[0162] Figure 2 The graph shows the relationship between the value of the polar term in the Hansen solubility parameter for organic solvents and the lithium ion conductivity of the LTOC after vacuum drying. The horizontal axis shows the value of the polar term in the Hansen solubility parameter for organic solvents δp (MPa 1 / 2 ). The vertical axis represents the lithium ion conductivity (mS / cm) of the LTOC after vacuum drying. In the comparative example, the lithium ion conductivity of the sample from which the organic solvent could not be removed by vacuum drying was assumed to be 0 mS / cm.

[0163] according to Figure 2 , the lithium ion conductivity of the vacuum-dried LTOC does not depend on the value of the polar term in the Hansen solubility parameter for the organic solvent. On the other hand, the lithium ion conductivity of the vacuum-dried LTOC depends on the functional group of the organic solvent. When the organic solvent is a hydrocarbon, or when the organic solvent has a chlorine group as a functional group, the dried LTOC has a high lithium ion conductivity. On the other hand, when the organic solvent has an ether group, a Si-OC group, a carbonyl group, an amino group or a hydroxyl group as a functional group, the vacuum-dried LTOC has a small lithium ion conductivity. That is, when the functional group of the organic solvent contains a heteroatom, the vacuum-dried LTOC has a small lithium ion conductivity. As heteroatoms, N, O, P and S can be cited. Although the detailed mechanism of action is unclear, if the organic solvent has a functional group that localizes the electron density, then in the functional group, the site where the electron density is localized will interact with the constituent elements of the LTOC, such as solvation. It is therefore believed that the organic solvent is strongly adsorbed on the surface of the LTOC particles and the structure of the LTOC is destroyed. As a result, it is estimated that the lithium ion conductivity is reduced in the solid electrolyte member of the comparative example. It is believed that the solid electrolyte material containing oxygen element and halogen element has a common tendency.

[0164] Industrial Applicability

[0165] The solid electrolyte composition of the present application can be used, for example, in the manufacture of an all-solid lithium secondary battery.

Claims

1. A solid electrolyte composition comprising: Oxyhalide solid electrolyte material containing oxygen and halogen, and Organic solvents, The organic solvent comprises at least one selected from a compound having a halogen group and a hydrocarbon, The oxyhalide solid electrolyte material includes at least one selected from Zn, Sn, Al, Sc, Ga, Bi, Sb, Zr, Hf, Ti, Ta, Nb, W, Y, Gd, Tb and Sm, and has lithium ion conductivity.

2. The solid electrolyte composition according to claim 1, wherein The oxyhalide-based solid electrolyte material includes at least one selected from F, Cl, Br, and I.

3. The solid electrolyte composition according to claim 1, wherein The oxyhalide-based solid electrolyte material includes Li, O, at least one selected from Ta and Nb, and at least one selected from F, Cl, Br, and I.

4. The solid electrolyte composition according to claim 3, wherein The oxyhalide-based solid electrolyte material includes at least one selected from a material containing Li, Ta, O, and Cl, a material containing Li, Nb, O, and Cl, and a material containing Li, Ta, Nb, O, and Cl.

5. The solid electrolyte composition according to claim 4, wherein The oxyhalide solid electrolyte material comprises Li, O, M and Cl, The M comprises at least one selected from Ta and Nb, The ratio of the number of moles of O to the number of moles of Cl is 0.16 or more and 0.35 or less, The ratio of the number of moles of Li to the number of moles of M is 0.6 or more and 2.4 or less.

6. The solid electrolyte composition according to claim 5, wherein The oxyhalide solid electrolyte material comprises a material selected from LiTaOCl4, LiNbOCl4 and LiTa 0.9 Nb 0.1 At least one of OCl4.

7. The solid electrolyte composition according to claim 1, wherein The compound having a halogen group has only a halogen group as a functional group.

8. The solid electrolyte composition according to claim 1, wherein The organic solvent contains a ring structure.

9. The solid electrolyte composition according to claim 8, wherein The organic solvent contains an aromatic compound.

10. The solid electrolyte composition according to claim 1, wherein The organic solvent comprises at least one selected from tetralin, ethylbenzene, mesitylene, pseudocumene, xylene, cumene, 1,2,4-trichlorobenzene, chlorobenzene, 2,4-dichlorobenzene, o-chlorotoluene, 1,3-dichlorobenzene, p-chlorotoluene, 1,2-dichlorobenzene, 1,4-dichlorobutane, 2,4-dichlorotoluene and 3,4-dichlorotoluene.

11. The solid electrolyte composition according to claim 1, wherein The organic solvent comprises at least one selected from tetralin, mesitylene, xylene, cumene, o-chlorotoluene, p-chlorotoluene, 1,4-dichlorobutane, 2,4-dichlorotoluene and 3,4-dichlorotoluene.

12. The solid electrolyte composition according to claim 1, wherein The oxyhalide-based solid electrolyte material does not substantially contain sulfur. 13 . A method for producing a solid electrolyte component, comprising the step of removing the organic solvent from the solid electrolyte composition according to claim 1 .

14. The method for producing a solid electrolyte component according to claim 13, wherein: The organic solvent was removed by drying under reduced pressure.

Citation Information

Patent Citations

  • Solid electrolyte composition, solid electrolyte-containing sheet, all-solid-state secondary battery, method for producing solid electrolyte composition, method for producing solid electrolyte-containing sheet, and method for producing all-solid-state secondary battery

    WO2018168505A1

  • Solid electrolyte composition and production method for solid electrolyte member

    CN112771626A

  • Methods to produce solid electrolyte and solid electrode composites

    US5190695A